PWE-441 Colonoscopy procedures with and without sedation and pain scores. (22nd June 2015) - Birdi, S; Stasinos, I; Muller, A
Abstract : Introduction: Retrospective data collection to compare pain scores during colonoscopy procedures performed with and without sedation in both Bowel cancer screening programme (BCSP) and Non bowel cancer screening programme (Non BCSP) patient groups. Method: Data collected retrospectively for all patients who underwent colonoscopy procedures at East Kent Hospitals NHS Trust from August 2014 to October 2014. Data collected from Unisoft in endoscopy department before C02 was introduced. Total number of colonoscopy procedures performed 1903 over 3 month period. 179 patients excluded because of incomplete endoscopy reports including comfort scores. Total number of patients included 1724. Number of patients in Non BCSP group and BCSP group were 1565 and 159 respectively. Pain score completed post colonoscopy procedure. Patient pain scores were recorded from 0–3 (no discomfort, minimal discomfort (One or two episodes of mild discomfort, well tolerated), moderate discomfort (More than two episodes of discomfort, adequately tolerated), Extreme or significant discomfort). Results: Non BCSP (Non Bowel Cancer screening programme) Group a) Sedated patients 1136 (72.58%), Male: female (486:650), Average age and Standard deviation (61.66, 13.4) b) Unsedated patients 429 (27.42%), Male: female (277:152), Average age and standard Deviation (71.5, 4.95) BCSP (Bowel cancer screening Programme) Group a) Sedated patients 104 (65%), (Male: female 49:55), Average age and standard deviation (72.5, 3.53) b) Unsedated patients 55 (35%), (Male: Female 45:10) Average age and standard deviation (67.1, 0.71) Pain scores for sedated and unsedated patients in Non BCSP and BCSP groups are shown in Table 1 below Conclusion: Unsedated colonoscopy is a safe, effective and well tolerated procedure in the right patient. Male gender is predominant in patients underwent colonoscopy without sedation in both BCSP and Non BCSP. Nearly 1/3 rd of patients in symptomatic Non BCSP and BCSP group completed the procedure without sedation without more discomfort than those received sedation (although this may reflect different groups of patients). Despite the used greater intervention in bowel cancer screening patients after pain scores with and without sedation were similar to the symptomatic group. Disclosure of interest: None Declared.